ANALISIS KEMAMPUAN BERPIKIR KREATIF MATEMATIKA PADA SISWA KELAS V SEKOLAH DASAR DI SD INPRES KARUNRUNG - Andriani, Indra; Rahmawati Patta; Hamzah Pagarra (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
This research is descriptive research using qualitative methods. This research aims to describe students' creative mathematical thinking abilities including indicators of fluency, flexibility, originality and detail in solving flat shape problems. This research used 20 subjects grouped into 3 subjects. The selection of research subjects was based on the acquisition of creative thinking ability test scores, namely high, medium and low scores, which then selected one student each to be used as research subjects. Meanwhile, the object of research is the answer sheet on the results of students' creative thinking ability tests guided by interview guidelines. The results of this research show that (1) on the fluency indicator, the three subjects were able to fulfill the indicators indicated by the ability to give a variety of correct and appropriate answers. (2) on the flexibility indicator, only two subjects were able to provide different methods but still produce the same results. (3) on the original indicator, it can be seen that on three questions there were two subjects who gave unusual answers and produced correct final scores. (4) on the elaboration indicator only two subjects were able to provide detailed answers and provide logical reasons for each steps to solve the problem. The conclusions in this research are (1) students' mathematical creative thinking abilities are still relatively low. (2) Based on the data obtained, the indicators that are still low are flexibility and originality. (3) factors that influence the low ability to think creatively are forgetfulness, rarely practicing, teachers rarely giving assignments, not daring to try new things.